Tripolar Tipologi Keagamaan dan Titik Temu Agama - Yunika Sari (UIN Sunan Gunung Djati Bandung, 2023)
This article discusses information related to tripolar typology and the study of religious intersections. The author uses qualitative research and library research, with descriptive analysis writing techniques. The discussion of this research includes the understanding of tripolar typology, namely exclusive, inclusive, and plural; then the meeting point of religions. This study concludes that this tripolar tripology consists of, firstly, an exclusive one that only admits its true religion while other religions are wrong; second, inclusive, which not only recognizes the true religion, but also gives freedom to other religions to acknowledge the truth of their religion; third, namely pluralism which respects the differences of religions while maintaining the characteristics of each religion. As for the meeting point of religions (kalimatun sawa), Shuon believes that all religions have similarities apart from differences. The similarity of religion lies in the esoteric aspect, the essence of all religions to God Almighty as the same point. And the difference from religion only lies in the exoteric aspect, namely the form of law or sharia determined by God.